Estudo da cadeia de suprimentos de portas prontas de madeira - Melo, Reymard Sávio Sampaio de (2010)
This master's thesis investigated the flows of material and information among participants of the supply chain of pre-fabricated wooden doors. The Brazilian literature on the topic presents different studies on supply chain mapping, however, few of them discuss issues related to supply chains on the country's Northeastern region. The supply chain investigated was choosen based on previous research projects carried out by the Grupo de Pesquisa e Assessoria em Gerenciamento na Construção Civil (GERCON), a construction management research group at the Federal University of Ceará, Brazil. Previous studies carried out by GERCON researchers, on low-income housing projects, had revealed numerous problems related to wooden doors and windows. Using the results of previous studies as a starting point, this thesis studied the pre-fabricated wooden doors and their supply chain which have all of its components pre-assembled by the supplier. The use of pre-fabricated wooden doors would theoretically reduce the number of activities performed at the construction site, and would result in a shorter installation time. The two-phase research comprised a preliminary study and two in-depth case studies about pre-fabricated wooden doors. The author carried out the case studies in two high rising buildings (one residential and one commercial) in the city of Fortaleza, Brazil, in order to investigate the supply chain of pre-fabricated wooden doors. Value stream maps were developed based on direct observation of the processes involved to fabricate and install the product at the supplier‟s plant and the construction site respectively, photos, and interviews with different professionals at the plant and at the site. Wooden doors presented problems related to the installation and final product quality regardless of the type of project. Some advantages of prefabricated elements were lost due lack of trust between contractors and suppliers, lack of consideration of preconditions necessary for successful site installation, and lack of standardization and tolerance management resulted in suboptimal solutions during the installation phase. Special attention should be paid to the interfaces between the prefabricated element and the other parts of the project, current means and methods should be revisited if the project is to fully take advantage of prefabrication. The lack of open communication and low levels of trust amongst the supply chain actors result in enormous amounts of waste (e.g., rework, wasted time, unnecessary handling, unnecessary use of resources) and diminished value to the client.